Studi Kritis Pasal 51 Ayat (1) UU Nomor 24 Tahun 2003 Juncto UU Nomor 8 Tahun 2011 tentang Mahkamah Konstitusi terhadap Perlindungan Hak Warga Negara Asing di Indonesia - Proborini Hastututi (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2016)
The results showed that the test of a law submitted by one or more foreigners are nominallythey are not allowed to submit the test. It was grounded because of the applicant's judicial review isonly allowed for the individual citizen, even if the foreign national has reason violated hisconstitutional rights and existing laws are considered contrary or inconsistent with the 1945Constitution, but they are in formal examinations can not be used as an applicant. Thus, theexamination material also can not be examined by the Constitutional Court. Important to knowthat the constitutional rights originating from 1945 is not only owned by the citizen but alsoforeigners. Therefore, constitusional loss can also be experienced by foreigners. Additionally, refer tothe practices of the International that the constitutional and judicial practices of other countries donot close access to the constitutionality of laws concerning human rights which are universallyrecognized and protected, although limited to the rights which by their nature do not involve therelationship of citizens to the State.